An interesting application of lung ultrasonography - Mayo, Paul H (BioMed Central, 2013)
In the previous issue of Critical Care, Raimondi and colleagues investigate whether lung ultrasonography has utility for the assessment of respiratory distress in the neonate. This commentary reviews the results and implications of their study.